2021
DOI: 10.1186/s12974-021-02113-2
|View full text |Cite
|
Sign up to set email alerts
|

The immune response and aging in chronic inflammatory demyelinating polyradiculoneuropathy

Abstract: Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) consists of various autoimmune subtypes in which the peripheral nervous system (PNS) is attacked. CIDP can follow a relapsing-remitting or progressive course where the resultant demyelination caused by immune cells (e.g., T cells, macrophages) and antibodies can lead to disability in patients. Importantly, the age of CIDP patients has a role in their symptomology and specific variants have been associated with differing ages of onset. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 133 publications
(174 reference statements)
1
12
0
Order By: Relevance
“…Apart for the increased level of IL-6 discussed above, the levels of TNF-α, IL-4 and IL-2 were also significantly higher in our patients with CIDP. Elevated levels of inflammatory cytokines such as IL-2, IL-6, TNF-α and B-cell activating factor in serum and CSF in CIDP patients have been reported in other studies [ 31 , 32 ]. In CIDP, an increased number of circulating activated T cells, increased levels of IL-2 and its soluble receptors (IL-2r) are found.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Apart for the increased level of IL-6 discussed above, the levels of TNF-α, IL-4 and IL-2 were also significantly higher in our patients with CIDP. Elevated levels of inflammatory cytokines such as IL-2, IL-6, TNF-α and B-cell activating factor in serum and CSF in CIDP patients have been reported in other studies [ 31 , 32 ]. In CIDP, an increased number of circulating activated T cells, increased levels of IL-2 and its soluble receptors (IL-2r) are found.…”
Section: Discussionsupporting
confidence: 52%
“…TNF-α may be associated with disruption of the blood–nerve barrier and demyelination [ 27 , 28 ]. Hagen et al [ 32 ] demonstrated that in CIDP there is an increase in macrophage clustering around endoneurial blood vessels, as well as an increase in TNF-α staining in macrophages located in close proximity to myelinated fibres. CD4+ and particularly CD8+ T cells have been identified in inflammatory nerve infiltrates in patients with CIDP.…”
Section: Discussionmentioning
confidence: 99%
“…Classical CIDP pathology is associated with macrophage and T cell infiltration in the peripheral nerves and nerve roots that results in segmental demyelination [10]. Histological studies in sural nerves from patients affected with CIDP found hypomyelination with immunoglobulin and complement deposition on the outer surface of Schwann cells and the compact myelin, onion bulb formation, abnormal Schwann cell morphology, and irregular paranodal loops [10]. However, these pathological findings are only present in a subset of patients, and most likely, different phenotypes associate with different immunopathological features [11].…”
Section: Cellular Immunitymentioning
confidence: 99%
“…The typical form of CIDP is a sensorimotor form with a chronic onset, symmetrical symptoms distribution, usually more proximal than distal [ 14 ]. In approximately 16% of patients with typical CIDP, the onset is sudden (acute-onset CIDP), with the greatest intensity of symptoms in less than 2 months [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The typical form of CIDP is a sensorimotor form with a chronic onset, symmetrical symptoms distribution, usually more proximal than distal [ 14 ]. In approximately 16% of patients with typical CIDP, the onset is sudden (acute-onset CIDP), with the greatest intensity of symptoms in less than 2 months [ 12 , 14 ]. The atypical forms of CIDP or CIDP variants include: the form with predominant sensory symptoms (sensory), including the chronic immune sensory polyradiculopathy (CISP) form, the form with the predominance of motor symptoms (motor CIDP), including the axonal motor form (MAMA, multifocal acquired motor axonopathy), with predominance of symptoms in the distal segments (DADS, distal acquired demyelinating symmetric neuropathy), asymmetric form (multifocal acquired sensory-motor neuropathy [MADSAM, multifocal acquired demyelinating sensors and motor neuropathy]) and focal (with the involvement of one or more nerves in one limb, with symptoms of involvement of the brachial or lumbosacral plexuses) [ 6 , 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%